Scoping review to identify and map non-pharmacological, non-surgical treatments for dysphagia following moderate-to-severe acquired brain injury - Signe Janum Eskildsen; Daniela Jakobsen; Christian Gunge Riberholt; Ingrid Poulsen; Derek John Curtis (BMJ Open)
Introduction Dysphagia is a common and critical consequence of acquired brain injury (ABI) and can cause severe complications. Dysphagia rehabilitation is transforming from mainly compensatory strategies to the retraining of swallowing function using principles from neuroscience. However, there are no studies that map interventions available to retrain swallowing function in patients with moderate-to-severe ABI.Objective To systematically map the accessible research literature to answer the research question: Which non-surgical, non-pharmacological interventions are used in the treatment of dysphagia in patients with moderate and severe ABI in the acute and subacute phase?Design Scoping review based on the methodology of Arksey and O’Malley and methodological advancement by Levac et al.Data sources MEDLINE, Embase, Cochrane Library, CINAHL, PsycINFO, Web of Science, OTseeker, speechBITE and PEDro were searched up until 14 March 2021.Eligibility criteria All studies reporting rehabilitative interventions within 6 months of injury for patients with moderate-to-severe ABI and dysphagia were included.Data extraction and synthesis Data was extracted by two independent reviewers and studies were categorised based on treatment modality.Results A total of 21 396 records were retrieved, and a final of 26 studies were included. Interventions were categorised into cortical or non-cortical stimulation of the swallowing network. Cortical stimulation interventions were repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation. Non-cortical were complex swallowing interventions, neuromuscular electrical stimulation, pharyngeal electrical stimulation (PES), sensory stimulation, strengthening exercises and respiratory muscle training.Conclusion This scoping review provides an overview of rehabilitative dysphagia interventions for patients with moderate and severe ABI, predominantly due to stroke, in the acute and subacute phase. Positive tendencies towards beneficial effects were found for rTMS, complex swallowing interventions, PES and cervical strengthening. Future studies could benefit from clear reporting of patient diagnosis and disease severity, the use of more standardised treatment protocols or algorithms and fewer but standardised outcome measures to enable comparison of effects across studies and interventions.